2010
DOI: 10.1186/1472-6963-10-216
|View full text |Cite
|
Sign up to set email alerts
|

Patient related factors in frequent readmissions: the influence of condition, access to services and patient choice

Abstract: BackgroundPeople use emergency department services for a wide variety of health complaints, many of which could be handled outside hospitals. Many frequent readmissions are due to problems with chronic disease and are preventable. We postulated that patient related factors such as the type of condition, demographic factors, access to alternative services outside hospitals and patient preference for hospital or non-hospital services would influence readmissions for chronic disease. This study aimed to explore t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
62
1
12

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 54 publications
7
62
1
12
Order By: Relevance
“…Patients with inadequate health literacy are generally those with fewer economic resources, have low English proficiency, are older with lower levels of basic literacy skills (Kirby et al 2012;Schillinger et al 2002). They are the ones who are less likely to independently navigate the health system or have the confidence to work with health professionals in taking up health-promoting behaviours (Kirby et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with inadequate health literacy are generally those with fewer economic resources, have low English proficiency, are older with lower levels of basic literacy skills (Kirby et al 2012;Schillinger et al 2002). They are the ones who are less likely to independently navigate the health system or have the confidence to work with health professionals in taking up health-promoting behaviours (Kirby et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that patients from disadvantaged areas are especially vulnerable to poor diabetes outcomes (Schillinger et al 2002) and they are often the people who experience more problems accessing and navigating the system and may result in them using the emergency department (ED) to manage their chronic disease (Kirby et al 2010). This paper aims to describe the views and experiences of patients regarding the multidisciplinary care they received for their diabetes and the facilitators and barriers to taking part in this care.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 In addition, some argue that hospitals should not be held accountable for readmissions because factors that contribute to readmissions often are not hospital factors (eg, postoperative complication) but instead are outpatient (eg, nurse unable to visit home) or patient (eg, not taking prescribed medications) factors and thus beyond the hospital's direct control. 14,15 Currently, 3 main strategies for ascertaining the potential preventability of hospital readmissions include the following: claims-based algorithms, medical record review, and structured interviews. Claims-based algorithms are perceived to be limited in identifying reasons for readmission.…”
mentioning
confidence: 99%
“…17,18 A predominância do sexo feminino encontrado nesta pesquisa é análoga ao que a literatura expõe. 18,19 Tal episódio pode ser justificado pela caracterís-tica cultural que a mulher carrega, pelos laços maternais, sendo vista como símbolo de cuidado.…”
Section: Discussionunclassified
“…Tal fato chama a atenção, pois o acompanhamento das DCNTs deve acontecer prioritariamente na APS, 17 levando a questionamentos sobre a influência do víncu-lo que este nível de atenção possui, uma vez que a aferição de sinais vitais é técnica básica para o cuidado ao idoso.…”
Section: Discussionunclassified